ANALISIS KINERJA PERBANKAN BERDASARKAN RASIO LIKUIDITAS - Fathurrahman, Fathurrahman (Nusantara Hasana Journal, 2022)
This study aims to describe whether a high current ratio reflects good banking performance. The type of research used in this research is descriptive research using a quantitative approach by conducting a literature review. The result of this research is that the effect of current ratio (liquidity) on ROA (profitability) is inversely proportional. The high current ratio illustrates the high level of liquidity. High liquidity results in high idle cash. It can be concluded that the relationship between the level of the current ratio and the company's return on assets is inversely proportional. If the current ratio level increases, the rate of return on assets will decrease. And vice versa, if the current ratio decreases, the return on assets will increase.